Agonist-antagonist muscle activation during drop jumps - Arai, A.; Ishikawa, M.; Ito, A. (European Journal of Sport Science, 2013)
Pre-programmed and stretch-induced muscle activities of agonist muscles can play important roles during stretch-shortening cycle exercises. It is still not clear how the antagonist muscles function when the drop and rebound intensities are varied during drop jump (DJ) exercises. The purpose of the present study was to examine the regulation of agonist-antagonist muscle activation during DJ with different drop and rebound heights. The subjects performed DJs with two drop heights (0.2 and 0.4 m) and three different efforts (maximal rebound height, 50% effort of maximal rebound height and landing without rebound). Ankle and knee joint angles, and vertical ground reaction force together with an electromyogram of the lower leg muscles (medial gastrocnemius [MG], soleus [SOL] and tibialis anterior [TA]) were measured simultaneously during DJ. Our results clearly showed that the pre-activation of the antagonist TA was increased with increasing rebound height. Our results further showed that the coactivations of agonist and antagonist muscles during the post-impact 30-ms phase were increased with increasing rebound height. These results suggested that not only the pre-programmed agonist MG muscle activation, but also the pre-programmed antagonist TA activation and the coactivation of the post-impact 30-ms phase may play important roles in the control of rebound height.